Local Labour Markets, Migration and Wage Determination: Theory and Evidence for the Wage Curve in New Zealand - Morrison, Philip; Papps, Kerry; Poot, Jacques (School of Management Working Papers, 2000)
Blanchflower and Oswald (1994) claim that there is a stable inverse relationship between the wages paid to workers and the local unemployment rate. Using micro data from a range of countries they find an unemployment elasticity of pay of around -0.1. We use a dynamic efficiency model based on Phelps (1994) to produce an upward-sloping locus of steady-state wage and employment rate outcomes. In our model, points along this locus are identified by local labour market shocks. In the long run, inter-regional equilibrium ensures that regions lie on a so-called Harris-Todaro condition, which is consistent with no net internal migration. Using a synthetic micro sample of 20,302 observations from the 1986, 1991 and 1996 New Zealand Censuses of Population and Dwellings, we then find support for this specification of the earnings equation. As predicted, the coefficient on the employment rate is positive, while the gross migration rate has a positive effect on wages. In contrast, Blanchflower and Oswald’s specification is not robust to controlling for the possible presence of simultaneity bias, due to the endogeneity of unemployment. Separate gender regressions reveal that males, but not females, exhibit a positive employment elasticity of pay, possibly due to the greater labour supply elasticity of the latter group. Evidence that the wages of less geographically mobile groups of workers are also more responsive to changes in the local unemployment rate is found when occupations of different skill levels are analysed. Finally, we use a procedure developed by Lang and Gottschalk (1996) to show that our data set has permitted a 41 % gain in efficiency of the estimation of the employment elasticity of pay over previous New Zealand studies that used aggregate data.